IHOR KOSTETSKYI AND EUGENE IONESKO: TYPOLOGY OF ARTISTIC THINKING - Semak, O. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article deals with the works of such famous playwrights as Ihor Kostetskyi and Eugene Ionesco. The comparison of the work of the Ukrainian playwright with the dramatic works of the world level made it possible to distinguish the laws that show that Ihor Kostetskyi's drama is a multi-faceted and ambiguous phenomenon in the literary process of the second half of the twentieth century. The study of the peculiarities of the literary heritage of I. Kostetskyi involves a profound analysis of the influence of the emigration factor on creative process of the writer. His close interweaving of universal, national, and moral issues was caused by life in emigration and the loss of Ukraine. The combination of Ukrainian mentality with the understanding of the philosophical concepts of the West allowed the playwright-emigrant to consider social and moral problems more panoramic. Using techniques such as phantasmagority of individual scenes, deconstructivistic distrust to language, the destruction of syntactics and paradigmatics and logical structural connections in some places allows us to characterize the poetics of I. Koste-tskyi’s style as an absurdity experiment based on the drama of the Baroque era.In the result of comparison of the heritage of Eugen Ionesco and Ihor Kostetskyi the author found that both dramatists rejected the canons of classical drama with its traditional plot, experimented with the form of works, the language of characters. The artistic material of their dramatic works unfolds through absurd situations that contrast with the world of reality.One of the problems raised by the authors is the problem of human communicability, which leads to leveling of the personality. Their verbal experiments are one of the factors in the creation of new generations of heroes. The dramatists did not abandon one of the main problems of existentialism - time as characteristics of human being.